Perceptual Anomalies in Schizophrenia: Integrating Phenomenology and Cognitive Neuroscience - Uhlhaas, Peter J. (Oxford University Press, 2007)
From phenomenological and experimental perspectives, research in schizophrenia has emphasized deficits in “higher” cognitive functions, including attention, executive function, as well as memory. In contrast, general consensus has viewed dysfunctions in basic perceptual processes to be relatively unimportant in the explanation of more complex aspects of the disorder, including changes in self-experience and the development of symptoms such as delusions. We present evidence from phenomenology and cognitive neuroscience that changes in the perceptual field in schizophrenia may represent a core impairment. After introducing the phenomenological approach to perception (Husserl, the Gestalt School), we discuss the views of Paul Matussek, Klaus Conrad, Ludwig Binswanger, and Wolfgang Blankenburg on perception in schizophrenia. These 4 psychiatrists describe changes in perception and automatic processes that are related to the altered experience of self. The altered self-experience, in turn, may be responsible for the emergence of delusions. The phenomenological data are compatible with current research that conceptualizes dysfunctions in perceptual processing as a deficit in the ability to combine stimulus elements into coherent object representations. Relationships of deficits in perceptual organization to cognitive and social dysfunction as well as the possible neurobiological mechanisms are discussed.